Perceived instructor affective support in relation to academic emotions and motivation in college - SAKIZ, GÖNÜL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2012)
The purpose of the present study was to examine the associations among perceived instructor affective support, academic enjoyment, academic hopelessness, behavioural engagement and academic help seeking in college classrooms. A self-report survey was administered to 277 college students enrolled in a teacher training department of a major university in Turkey. Structural equation modelling was used for data analysis. Perceived instructor affective support, either directly and/or indirectly, related to all emotional and motivational variables presented in the structural model. Findings signify the necessity of providing affectively supportive learning environments not only in K12 classrooms but also in college classrooms. The implications for practice and future research as well as the limitations are discussed.
Keywords: perceived instructor affective support; academic enjoyment; academic hopelessness; behavioural engagement; academic help seeking; teacher training; TEACHER-STUDENT RELATIONSHIP; ACHIEVEMENT EMOTIONS; NONVERBAL IMMEDIACY; CHILD RELATIONSHIPS; HELP-SEEKING; CLASSROOM; ENGAGEMENT; BEHAVIOR; PERCEPTIONS; IMPACT